We have the following equation given:
![4x=7y-z](https://img.qammunity.org/2023/formulas/mathematics/college/db2h0pxv8miawc8h9sfj1c8cnrwvepvag1.png)
We need to solve for y when x=8 and 7z=-4. If we solve for y we got:
![7y=4x+z](https://img.qammunity.org/2023/formulas/mathematics/college/727zac8dtqzjyn8ac8b5afk5lwwlagb3kh.png)
And dividing both sides by 7 we got:
![y=(4x+z)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/7d5mm6u9pms54nlrsa2j7r3q23xrfrqi6x.png)
We can use the condition 7z=-4 in order to solve for z and we got:
![z=-(4)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/zk45ygls3cld83ela55xvz5o5zacnqnipr.png)
Now we can replace x and z in order to solve for y and we got:
![y=(4(8)+(-(4)/(7)))/(7)=(32-((4)/(7)))/(7)=(220)/(49)](https://img.qammunity.org/2023/formulas/mathematics/college/t3debirzg4j1wj6dlegorey6danr3t3fjc.png)